ANALISIS PRODUK PAKAIAN JADI BLUS BATIK WANITA: (Survei di Pusat Grosir Surabaya) - Atiqoh Atiqoh (Buana Pendidikan, 2011)
The research aims to know and analyse the ready wear clothes product of blouse batik to standard size SNI, price, brand and motif. The research method used is descriptive method with survey technique approach. The ressearch started on oktober until December 2011. The sample took 120 persons. The taking technique of the sample was done in Accidental sampling. The validity test used 3 expert lectures by trying out the instrument. The collecting data technique used questioner, interview, documentation and observation. The analyse data used descriptive analyse on the presentation. The questioners consist of 22 questions. In reality, there two questions were not valid, they were 9 and 18, the total of questions were 20 questions. The validity and realibility used SPSS 12.00 and got value of r=0,8791. It meant the realibility was very realible. Not all the brand of the ready wear clothes product blouse batik are using the SNI standard. The price to be main focus for consumers on buying of the readu wear clothes product blouse batik. The much of brand responden’s choosing are the local brand like number 15. Much of the motif to choose are the line motif.